Influencia de la inteligencia emocional de los gerentes en la retención del talento humano de una empresa de entretenimiento cinematográfico, Trujillo 2016 - Liza Gamboa, Johanna Katherine (2016)
The following work is the result of the study of the problem, how does the emotional intelligence of the managers influence the retention of the human talent of a film entertainment company Trujillo 2016? And in response, two hypotheses are presented, which by means of chi square will measure the relationship between the two variables, one is the research hypothesis and the other the null hypothesis that contradicts the first. The research hypothesis presented is that the emotional intelligence of the managers directly influences the retention of the human talent of a film entertainment company Trujillo 2016. The main objective of this research is to identify how it influences the emotional intelligence of managers in retaining human talent CinePlanet Trujillo-Center complex, which will be achieved found by using the dimensions of the variables emotional intelligence and retaining talent human with their respective indicators. The research design is descriptive - correlational; the sample is universal, which consists of two groups, the first grouped the 49 employees of the complex and the second sample considered at 5 managers evaluated in the first, all of them were given a survey and collection technique data for further analysis of the results. Therefore, according to the results obtained, it is concluded that managers handled properly some dimensions of emotional intelligence and this significantly influences the retention of human talent in the company CinePlanet Trujillocenter, so it is recommended trainings members of management to strengthen the management of their emotional intelligence.